A Study on Teaching Chinese Second Language Interjection Based on PACE Teaching Model: 基于PACE教学模式的汉语二语叹词教学研究 - Lishen, Yu; Qingqing, Kong (Published by Confucius Institute UNS, 2000)
The PACE teaching model combines the advantages of teaching a second language explicit grammar and implicit grammar. The PACE teaching model is introduced comprehensively, and the Chinese interjection